REFLEKSI TERHADAP PEMBELAJARAN KELAS DI SMP ISLAM AL AZHAR 14 SEMARANG:: Pendekatan School Knowledge dan Action Knowledge - Dwi Istiyani; Esti Zaduqisti; Ely Mufidah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2012)
This research tried to reflect on learning activities done by teachers and students in classroom. What happens to the pattern of teaching in the class at the school, and whether teaching in the class at al-Azhar Islamic SMP 14 Semarang has reached the level of action knowledge or it is still at school knowledge are the problems to answer in this research. This research used the approach offered by Douglas Barnes, the school knowledge and action knowledge. The result shows that the combination of the two approaches (school knowledge and action knowledge) done at SMP Islam Al Azhar 14, is upon the two approaches initiated by Douglas Barnes. According to Barnes, in general, students learn new knowledge at school level, the students only gain knowledge of it, for example, students are only able to answer teacher’s questions, exam questions, and exercises, but they do not use that knowledge, or even forget it. He said that ideally, learning in the class should extend to learning by doing. Students do not only master the knowledge at the time in the classroom (school knowledge), but they also already have to use that knowledge in their personal area in the form of the action (action knowledge). In action knowledge, students’ perspective on the world can be changed, so that they will be able to take their own life goals.